2006
DOI: 10.1210/jc.2005-2785
|View full text |Cite
|
Sign up to set email alerts
|

Serum Profiles of Free and Conjugated Neuroactive Pregnanolone Isomers in Nonpregnant Women of Fertile Age

Abstract: The levels of conjugated PI were from one to almost three orders of magnitude higher in comparison with the free steroids. The results indicate that a substantial proportion of the progesterone is metabolized in the sequence progesterone-->5beta-dihydroprogesterone-->P3alpha5beta-->conjugated P3alpha5beta. The sulfation of PI and particularly of P3alpha5beta moderates the levels of free PI and restrains estradiol biosynthesis via progesterone degradation. PI including the conjugates reflected changing progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…The obvious explanation is that some isoallopregnanolone has been metabolized to allopregnanolone. This theory is supported by earlier findings showing that allopregnanolone and isoallopregnanolone serum concentrations are highly correlated both during the follicular and the luteal phase of the menstrual cycle (Havlikova et al 2006). Furthermore, the 3alpha hydroxylase is effective in both direction and when allopregnanolone is given to animals there is an increase in isoallopregnanolone concentration so one can expect that when isoallopregnanolone is given allopregnanolone should increase (Vallee et al 2000).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The obvious explanation is that some isoallopregnanolone has been metabolized to allopregnanolone. This theory is supported by earlier findings showing that allopregnanolone and isoallopregnanolone serum concentrations are highly correlated both during the follicular and the luteal phase of the menstrual cycle (Havlikova et al 2006). Furthermore, the 3alpha hydroxylase is effective in both direction and when allopregnanolone is given to animals there is an increase in isoallopregnanolone concentration so one can expect that when isoallopregnanolone is given allopregnanolone should increase (Vallee et al 2000).…”
Section: Discussionsupporting
confidence: 64%
“…The study was carried out in the follicular phase of the menstrual cycle when the endogenous concentrations of isoallopregnanolone and allopregnanolone are low. The baseline endogenous concentration obtained in the present study is in the upper range of concentrations reported in the literature when using HPLC/RIA and gas chromatography-mass spectrometry as analytical techniques (Romeo et al 1998;di Michele et al 2003;Schule et al 2003;Murphy et al 2004;Havlikova et al 2006). The concentrations measured in the present study are also higher than those obtained during the mid follicular phase in women at noon using the same assay method as in the present study (0.22 ± 0.77 nmol/l (mean ± SD), range 0.1 to 1.1 nmol/l, n=77, unpublished results).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Some reports indicate that in addition to the brain's in situ synthesis, circulating PIs penetrate the blood-brain barrier (Bixo et al 1997, Corpechot et al 1997. Although several studies have brought information to light regarding the levels of PI in humans, only a small number have included data regarding the respective polar conjugates (Mickan & Zander 1979, Hill et al 2000, Havlikova et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Mean physiological levels of allopregnanolone in healthy women are 0.3-1.9 nmol/l in the follicular phase and 2.1-3.7 nmol/l in the luteal phase [10,[21][22]. In humans suffering from acute stress, endogenous allopregnanolone levels have been shown to rise from 1.0 to1.3 nmol/l and the change was statistically significant [14].…”
Section: Discussionmentioning
confidence: 99%